2019
DOI: 10.1016/j.brs.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of the effects of transcranial direct current stimulation (tDCS) on episodic memory

Abstract: A Systematic Review and Meta-Analysis of the Effects of Transcranial Direct Current Stimulation (tDCS) on Episodic Memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
88
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(103 citation statements)
references
References 74 publications
13
88
0
2
Order By: Relevance
“…Here, corroborating previous publications using the same sample (Kolskår et al, 2020;, we found no significant associations between tDCS group (sham and experimental) and cognitive improvement, nor tDCS group by session interactions on TVA performance, providing no support for a beneficial effect of tDCS. These results are in lines with a recent review and meta-analysis study reporting limited effect of tDCS in the context of memory training (Galli et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Here, corroborating previous publications using the same sample (Kolskår et al, 2020;, we found no significant associations between tDCS group (sham and experimental) and cognitive improvement, nor tDCS group by session interactions on TVA performance, providing no support for a beneficial effect of tDCS. These results are in lines with a recent review and meta-analysis study reporting limited effect of tDCS in the context of memory training (Galli et al, 2019).…”
Section: Discussionsupporting
confidence: 92%
“…These results are in lines with a recent review and meta-analysis study reporting limited effect of tDCS in the context of memory training (Galli et al 2019). Several methodological considerations need to be highlighted while interpreting our results.…”
Section: Discussionsupporting
confidence: 92%
“…We have shredded insights about ineffective combinations of certain tDCS parameters for modulating the SPE, while overcoming sensible weakness of previous studies. Moreover, given the issues of reproducibility in cognitive neurosciences (Szucs and Ioannidis, 2017), and the current state of the art of NIBS, with non-trivial evidence collected that challenges reliable effects of a single session of tDCS on behavior (Bestmann et al, 2015;Horvath et al, 2015;Parkin et al, 2015;Medina and Cason, 2017;Galli et al, 2019), the call for dissemination of results like the ones reported here becomes paramount (Filmer et al, 2019).…”
Section: Discussionmentioning
confidence: 95%